Equivalent biaxial strain evaluation in small punch testing using acoustic emission. (April 2021) - Pullin, Rhys; Jenkins, Ifan; Cernescu, Anghel; Edwards, Allen
The small punch test initially used mainly in the nuclear sector proved to be an efficient method of estimating the mechanical properties of materials, including fracture toughness. In general, the fracture toughness is estimated based on a correlation with equivalent biaxial fracture strain. However, the latter depends on knowing the onset of the unstable fracture. In this article, the acoustic emission technique is used within the small punch test for estimating the unstable fracture initiation and determining the corresponding punch displacement from the load–displacement curve. Although, the acoustic emission signal can be slightly altered due to the location of the sensor, the results confirm the potential of the acoustic emission technique for detecting the onset of the unstable cracking and thus accurately estimating the equivalent biaxial fracture strain. The accumulated energy during the small punch test is one of the relevant acoustic emission parameters in estimating the fracture onset since it can be associated with the accumulated strain energy released by the deformed material.